Effect of alumina (Al2O3) addition on the calcium fluoroaluminosilicate based bioglass ceramics derived from waste materials - Ismail, Nur Quratul Aini; Sa’at, Nor Kamilah; Mohd Zaid, Mohd Hafiz; Zainuddin, Norhazlin; Mayzan, Mohd Zul Hilmi (Elsevier, 2022)
Bioactive glass (BG) is well known as materials that have ability to form hydroxyapatite layer (HA) that accelerates bonding between bone tissues indicating a good biological response. However, previous BG with composition of SiO2-CaO-Na2O-P2O5 system exhibit lower mechanical strength. Current study is to investigate the effect of alumina (Al2O3) in the 44SiO2-(20-x) Na2O-24CaO-6P2O5-6CaF2-xAl2O3 system where x = (0,3,6, and 9 wt%) towards its mechanical performance. Structural and microstructural factor were analyzed by x-ray diffraction (XRD) and scanning electron microscopy (SEM), meanwhile the density of glass ceramic samples was measured by Archimedes’ method. Subsequently, it was found that Al2O3 with higher composition that sintered at 950 °C has excellent results in term of density measurement. XRD analysis also has confirmed the increase of crystallization of anorthite, fluorapatite and nacaphite along with the rise of Al2O3 concentration. SEM analysis at the same time shows the morphology of agglomeration and irregular shape with a variation on size of sintered glass ceramics.